HIV/AIDS education and persons with special needs (2011)
HIV AIDS has become a threat to human existence especially in developing countries like Nigeria, although, several attempts have been made by both governmental and non-governmental to prevent it. These attempts are commendable, but the persons with special needs in our society seem to be neglected virtually in all awareness campaign programmes aimed at reducing at-risk practices among members of the society. It is evident from observation that sex education is not included in the curriculum for persons with special needs, they are not encouraged by stakeholders to attend voluntary HIV AIDS counselling and tests. These make at risk HI V AIDS practice very high among them. Based on these findings, the following recommendations are given: HIV AIDS education should be included in the curriculum for persons with special needs, the quality of life of persons with special needs would be a good Step towards reducing their at-risk practices, voluntary HIV AIDS counseling, tests and referral opportunities should be made available to them and there should be collaboration among the government and other stakeholders in order to combat HIV AIDS at risk behaviours among persons with special needs. This paper examined the level of HIV/AIDS awareness, at risk practices and preventive education among persons with special needs.